The Effect of Realistic Mathematics Education Approach Assisted by Interactive Multimedia Articulate Storyline on Reasoning Ability and Self Confidence - Ariffah, Eko Yunia Nur; Rusnilawati (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
Monotonous, less fun mathematics learning activities make students easily bored and not interested in participating in learning. Such learning does not train students’ reasoning abilities. This study aims to analyse whether the application of the Realistic Mathematics Education approach assisted by interactive multimedia articulate storylines can overcome the lack of reasoning skills and self-confidence. This type of research is quantitative. The design of this research is quasi-experimental design. This study used data collection techniques including observation, tests, questionnaires, and documentation. The data analysis technique used is the normality test, homogeneity test, t-test, and ANOVA test. The results of this study indicate that there is a significant effect of using the Realistic Mathematics Education approach assisted with interactive multimedia articulate storylines on reasoning abilities and self-confidence.